Forensic reconstructive hematology in Brazil (Research, Society and Development, 2023)
Reconstructive Forensic Hematology is the discipline responsible for the morphological study of bloodstains found at the crime scene, in order to infer the dynamics of the criminal act. The aim of this study was to conduct a narrative literature review to learn about Brazilian studies in Forensic Reconstructive Hematology. A search was performed in the Google Scholar database with the combination of descriptors: “bloodstains”, “hematology”, “forensics” and “patterns”. No specific period was estimated and only national works that were available in full and that dealt with theoretical or practical works on reconstructive Forensic Hematology were selected. It can be seen that most of the works included case reports in police incidents, abstracts or conclusion works and few experimental or observational works. With this, it was possible to conclude that the discipline is young in the country and needs more research incentive in the area and police appreciation, having potential to help justice and society.